Open Science in Africa: What policymakers should consider - Chiware, Elisha R. T.; Skelly, Lara (Frontiers in Research Metrics and Analytics, 2022)
As Open Science (OS) is being promoted as the best avenue to share and drive scientific discoveries at much lower costs and in transparent and credible ways, it is imperative that African governments and institutions take advantage of the momentum and build research infrastructures that are responsive to this movement. This paper aims to provide useful insight into the importance and implementation of OS policy frameworks. The paper uses a systematic review approach to review existing literature and analyze global OS policy development documents. The approach includes a review of existing OS policy frameworks that can guide similar work by African governments and institutions. This critical review also makes recommendations on key issues that Africa should consider in the process of OS policy development. These approaches can be widely used as further foundations for future developments in OS practices on the continent.